Fabrication and Characterization of Partial Bio-nano-silica Inclusion in Fibre-Reinforced Concrete for High-performance Applications - D. Vivek; C. Aravind; S. Gokulkumar; M. Aravindh; Yalew Asres (Advances in Polymer Technology)
Ultra-high-performance fibre-reinforced concrete (UHPFRC) is a specialized type of concrete (to create a very dense matrix) that is used for both new construction and renovation projects in order to improve the lifespan of structures. Researchers analyse and evaluate only the microstructure, porosity, and fresh and hardened concrete properties of UHPFRC but limited their exploration on the reduction of the mechanical properties of UHPFRC due to the presence of metallic particles and micro-fractures that occur during the generation of hydrogen. Hence, the present study aims to eliminate the existing problem by hybridization approach (mixing of bio-nano-silica (nS) and polypropylene) with different percentages to further improve the strength properties of UHPFRC. The result showed that the compressive strength is increased by 15.5% compared to traditional concrete due to the filling ratio of nS in the pores of the concrete; in addition, the fibre’s surface and roughness also contributed to the strength enhancement.